Problematika Waiting List Dalam Penyelenggaraan Ibadah Haji Di Indonesia - Nida Farhan (Jurnal Studi Agama dan Masyarakat, 2016)
This study raised the question of: (1) The problems that caused the waiting list in the organization of the hajj in Indonesia. (2) How to protect against regular pilgrims who were on a waiting list. (3) The solution was done to address these problems. This study is a library research nuanced on normative and descriptive study. Causes of the waiting list in the juridical aspect has not been any solid juridical basis; the philosophical aspects, and the sociological aspects. The absence of legal protction arrangements for the prospective pilgrims who were on a waiting list showed vacancy norm. Solution in juridical aspect formulation should be no additional principles of the organization of the hajj, the philosophical aspect, good organization of the hajj and religious awareness prospective pilgrims should be straightened out again, and the sociological aspect can be done by: added the Indonesian hajj quota, that no misuse of fatwa on bailout hajj, asked perform of pilgrimage only for those who want to repeat hajj, muslims are capable directed to charity, straighten the intention pilgrimage, improve exemplary scholars and leaders, as well as separating the Hajj organizers between regulators, operators, and evaluators.